Step 1: Decompose the integrand.
Consider the integral:
\[
I = \int \frac{e^{4x} - 1}{e^{4x} + 1} \, dx.
\]
We can simplify the integrand by rewriting it as:
\[
\frac{e^{4x} - 1}{e^{4x} + 1} = 1 - \frac{2}{e^{4x} + 1}.
\]
Thus, the integral becomes:
\[
I = \int \left( 1 - \frac{2}{e^{4x} + 1} \right) \, dx = \int 1 \, dx - 2 \int \frac{1}{e^{4x} + 1} \, dx.
\]
Step 2: Evaluate the first term.
The first integral is straightforward:
\[
\int 1 \, dx = x.
\]
Step 3: Solve the second integral using substitution.
To solve the second integral, let:
\[
u = e^{4x} + 1.
\]
Then, the derivative of \( u \) is:
\[
du = 4e^{4x} \, dx \quad \Rightarrow \quad \frac{du}{4} = e^{4x} \, dx.
\]
Substitute into the integral:
\[
\int \frac{1}{e^{4x} + 1} \, dx = \frac{1}{4} \int \frac{1}{u} \, du = \frac{1}{4} \ln|u| + C = \frac{1}{4} \ln|e^{4x} + 1| + C.
\]
Step 4: Combine the results.
Now, substitute the results of both integrals:
\[
I = x - \frac{1}{2} \ln|e^{4x} + 1| + C.
\]
Conclusion:
Thus, the value of the integral is:
\[
\boxed{x - \frac{1}{2} \ln|e^{4x} + 1| + C}.
\]